A control problem related to the parabolic dominative p-Laplace equation. (June 2020) - Høeg, Fredrik Arbo; Ruosteenoja, Eero
Abstract: We show that value functions of a certain time-dependent control problem in Ω × ( 0, T ), with a continuous payoff F on the parabolic boundary, converge uniformly to the viscosity solution of the parabolic dominative p -Laplace equation 2 ( n + p ) u t = Δ u + ( p − 2 ) λ n ( D 2 u ), with the boundary data F . Here 2 < p < ∞, and λ n ( D 2 u ) is the largest eigenvalue of the Hessian D 2 u .